The Effect of STEM Integrated Inquiry Models in Improving Student Science Learning Outcomes (A Meta-Analysis) - Dhanil, Muhammad; Mufit, Fatni; Asrizal, Asrizal; Putri, Fina Afriani (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
21st-century learning emphasizes the mastery of knowledge as a whole through the investigation of several points of view of knowledge, one of which is inquiry and STEM models. This study aims to determine the magnitude of the size of 20 studies on the effect of STEM-integrated inquiry models on science learning and learning outcomes. The moderator variables considered are education level and type of publication. The analyzed studies were obtained from Google Scholar and ERIC databases between 2013 and 2023. The results of the analysis showed that the influence of the STEM integrated inquiry model in physics learning on student learning outcomes had an average effect size value of 0.78 which was included in the medium category, based on 20 studies that had been collected. The distribution of studies discussing STEM-integrated inquiry models was most found in 2020 and international journals. The influence of STEM looks different at each level of education, with a significant dominance of influence occurring at the high school level.